Tracking Magma‐Crust‐Fluid Interactions at High Temporal Resolution: Oxygen Isotopes in Young Silicic Magmas of the Taupō Volcanic Zone - Shane M. Rooyakkers; Kevin Faure; Isabelle Chambefort; Simon J. Barker; Hannah C. Elms; Colin J. N. Wilson; Bruce L. A. Charlier (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Oxygen isotopes are useful for tracing interactions between magmas, crustal rocks and surface‐derived waters. We use them here to consider links between voluminous silicic magmatism and large‐scale hydrothermal circulation in New Zealand's central Taupō Volcanic Zone (TVZ). We present >350 measurements of plagioclase, quartz, hornblende and groundmass glass δ18O values from 40 eruptions from three discrete magmatic systems: Ōkataina and Taupō calderas, and the smaller Northeast Dome system. For each mineral, mean δ18O values vary by ∼1‰ (δ18Oplag = +6.7–7.8‰, δ18Oqtz = +7.7–+8.7‰, δ18Ohbl = +5.4–+6.4‰, δ18Oglass = +7.1–+8.0‰), and inter‐mineral fractionations mostly reflect high‐temperature equilibria. Outliers (e.g., ∼+6‰ or >+10‰ plagioclase) represent contaminants incorporated on short‐enough timescales to preserve disequilibrium (∼102 yrs for plagioclase). Melt δ18O values calculated from phenocrysts are ∼+7.3–+8.0‰. Where multiple magmas were involved in the same eruption their δ18Omelt values are indistinguishable, implying that their parental mushes were isotopically well‐mixed. However, small (≤0.5‰) but consistent δ18Omelt value gradients occur over millennial timescales at Ōkataina and Taupō, with short‐term ∼0.4–0.5‰ decreases in δ18Omelt values over successive post‐caldera eruptions correlating with increases in 87Sr/86Sr. These changes reflect tens of percent assimilation of a mixture of hydrothermally altered silicic plutonic material and higher‐87Sr/86Sr greywacke. These examples represent the first evidence for assimilation of altered crust into TVZ magmas. The subtle and short‐lived isotopic signals of these interactions are only recognized through the high temporal resolution of the TVZ eruptive record and complementary radiogenic isotope data. Similar interactions may have been obscured in other nominally high‐ or normal‐δ18O magmatic systems.